The endoplasmic reticulum protein HSPA5/BiP is essential for decidual transformation of human endometrial stromal cells - Fernández, Laura del Carmen (2024)
Decidualization denotes the process of inflammatory reprogramming of endometrial stromal cells (EnSC) into specialized decidual cells (DC). During this process, EnSC are subjected to endoplasmic reticulum (ER) stress as well as acute cellular senescence. Both processes contribute to the proinflammatory mid-luteal implantation window and their dysregulation has been implicated in reproductive failure. Here, we evaluated the link between ER stress, decidual differentiation and senescence. In-silico analysis identified HSPA5 gene, codifying the ER chaperone BiP, as a potentially critical regulator of cell fate divergence of decidualizing EnSC into anti-inflammatory DC and pro-inflammatory senescent decidual cells (snDC). Knockdown of HSPA5 in primary EnSC resulted both in decreased expression of DC marker genes and attenuated induction of senescence associated β-galactosidase activity, a marker of snDC. Stalling of the decidual reaction upon HSPA5 knockdown was apparent at 8 days of differentiation and was preceded by the upregulation of ER stress associated proteins IRE1α and PERK. Further, HSPA5 knockdown impaired colony-forming unit activity of primary EnSC, indicative of loss of cellular plasticity. Together, our results point to a key role for HSPA5/BiP in decidual transformation of EnSCs and highlight the importance of constraining ER stress levels during this process.